Simulation of forced vibrations of fluid free surface in spacecraft tanks - Горелова, Кристина Витальевна (Eastern-European Journal of Enterprise Technologies, 2013)
Studying the free surface behavior in various flight conditions of spacecraft (SC) is one of the most important tasks of innertank hydrodynamics and the dynamics of this surface allows determining the nature of fuel reorientation. Fluid motion in rectangular-shaped SC tank under constant horizontal disturbing force is considered in the paper. In case of translational acceleration of tank there are no studies on the motion nature of free surface of fluid. In the paper such tasks are proposed to solve by dividing the potential of fluid speed by the relative component of speed potential relative to tank and its walls. This provision is the basis for analytical researches. The paper also gives the adaption of the proposed model to existing conditions and results of numerical calculations. This paper gives an algorithm for calculating the profile of free surface of liquid for flat tanks depending on the values of relative loading under a uniformly accelerated motion of tank with acceleration at various points of time. It was found that for approximate estimation, the value of tank bottom baring can be determined by constructing the points of intersection of free surface profile with a profile of the tank bottom.